Overview of Knowledge about the Lactational Amenorerage Method in Breastfeeding Mothers - Salama Sely; Joko Prasetyo (STRADA : Jurnal Ilmiah Kesehatan, 2023)
The users of modern contraceptives in Indonesia are much more than the use of natural contraceptives, especially the lactation amenorrhea method. Indonesia had 64,133,347 million active family planning participants in 2012. The lactational amenorrhea method is a contraceptive method that relies on exclusive breastfeeding without providing additional food or drinks for 6 months. The aim of the study was to describe knowledge about the method of lactational amenorrhea in breastfeeding mothers in Waiselang Hamlet, Kairatu Village, Kairatu District, West Seram Regency in 2023. This research was a descriptive study using a cross-sectional method, the research sample was determined using the total sampling method, totaling 55 people. Sampling was carried out by means of total sampling. The research instrument used a questionnaire, and used univariate analysis.